THE PUBLIC DEFENDER AS A INSTRUMENT FOR THE EFFECTIVENESS OF HUMAN RIGHTS: A GUARANTEE OF THE FUNDAMENTAL RIGHT OF ACCESS TO JUSTICE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article analyzes the normative acts that deal with the performance of the Public Defender's Office in the promotion of Human Rights, notably as a guarantee of the fundamental right of access to justice. The main scope is to provide an overview of constitutional and legal provisions in relation, mainly, to Organization of American States Resolutions 2656/11, 2714/12, 2801/2013, 2821/14, 2887/2016 and 2928/2018 - OAS, exposing its practical and theoretical scope. Bibliographic research was carried out on works by the authors COMPARATO (2008), CORGOSINHO (2014), DINAMARCO (2005), MARTINS (2021), MENDES (2008), PIOVESAN (2008), SILVA (2005) and WEIS (2006), among others, highlighting the interpretation and application of the relevant legal provisions. Considering that access to justice is not an end in itself, but a guarantee for the effective exercise of other fundamental rights, it is concluded that the relevance of the Public Defender's Office in the promotion of human rights is related to the Dignity of the Human Person as one of the foundations of the Federative Republic of Brazil.